Evaluating the Efficiency of Metsulfuron-Methyl: The Role of Rice Cultivation Practices in Controlling Monochoria vaginalis - Sintho Wahyuning Ardie; Hariyadi; Kansa Dianti Putri; Guntoro, Dwi (Department of Agronomy and Horticulture, IPB University, 2024)
Monochoria vaginalis is an invasive weed that thrives in rice paddies across Indonesia. Herbicide control is challenging since Monochoria vaginalis is known to be sulfonylurea-resistant in Indonesian rice fields. This weed is highly competitive, with a rapid growth pattern that may diminish rice production. Metsulfuron-methyl, a widely used herbicide, can potentially eliminate sensitive weeds at low dosage levels. This study aimed to identify the optimal dosage of metsulfuron-methyl for controlling Monochoria vaginalis and assess the impact of monoculture rice growing patterns and herbicide application in controlling weeds. The experimental design was a split-plot design with four replications, conducted from June to July 2023 in the Cikabayan Greenhouse at IPB University. The major plot was the Monochoria vaginalis accession: exposed or not exposed to herbicide, consisting of seven sites. The subplot represented the dosage of the active ingredient (a.i.) metsulfuron-methyl: 0, 1, 2, 4, 8, 16, and 32 g.ha-1. In addition to the field experiments, interviews were performed with five farmers from each of the seven Monochoria vaginalis sample accessions to assess rice planting patterns and herbicide usage history. The results showed that metsulfuron-methyl at 1 g.ha-1 reduced weed populations by over 50% in rice accessions Bugel, Palumbonsari, and Ciasem Hilir. Variability in Monochoria vaginalis indicated resistance to metsulfuron-methyl, necessitating greater dosages up to 8 g a.i. per ha-1 for Pasirkaliki and Rancajaya accessions. Our study also indicated that some areas could use lower dosages of herbicides to effectively control Monochoria vaginalis. In contrast to other places that required larger, three-yearly dosages of 100 to 125 g.ha-1, Bugel, Palumbonsari, and Ciasem Hilir used a twice-yearly dosage of 20 g.ha-1. These findings highlight the importance of tailored herbicide application strategies based on local resistance patterns and historical herbicide use to manage Monochoria vaginalis effectively.